2009
DOI: 10.1016/j.compscitech.2009.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of carbon nanotube-reinforced epoxy: Correlation between viscosity and elastic modulus

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. abstractWe report the synthesis and characterization of nanocomposite thin films consisting of single-walled ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…4 b. Generally a rising trend is observed in tensile modulus of epoxy matrix composites by adding CNTs [39,40,64]; for example, the elastic modulus increased continuously in composites containing coiled CNTs [60] and SWCNTs, DWCNTs and MWCNTs, both un-treated and NH 2 -treated, increased the tensile modulus of epoxy matrix composites [41,42]. In an interesting study, 0.5wt% MWCNTs were incorporated in epoxy matrix with different matrix stiffness values by varying the quantity of curing agent; it was found that the effect of MWCNTs was significant in ductile matrix which gradually reduced with an increase in the stiffness of the matrix [65].…”
Section: 22tensile Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…4 b. Generally a rising trend is observed in tensile modulus of epoxy matrix composites by adding CNTs [39,40,64]; for example, the elastic modulus increased continuously in composites containing coiled CNTs [60] and SWCNTs, DWCNTs and MWCNTs, both un-treated and NH 2 -treated, increased the tensile modulus of epoxy matrix composites [41,42]. In an interesting study, 0.5wt% MWCNTs were incorporated in epoxy matrix with different matrix stiffness values by varying the quantity of curing agent; it was found that the effect of MWCNTs was significant in ductile matrix which gradually reduced with an increase in the stiffness of the matrix [65].…”
Section: 22tensile Propertiesmentioning
confidence: 94%
“…For example, improvement in tensile properties has been shown in epoxy matrix composites containing CNTs in limited quantities, i.e. up to 2.0wt% [38][39][40] as well as in large quantities, i.e. up to 8.0wt% [40].…”
mentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have received much attention in the last years as they are suitable to increase mechanical properties and thermal stability of polymer matrices [7–13]. Furthermore, their cost has been considerably reduced and this has allowed introduction of CNTs at industrial level.…”
Section: Introductionmentioning
confidence: 99%
“…What makes CNTs very interesting for composites is that even with a relatively low level of loading (ca. 0.1-1 wt%), improvements in mechanical properties of polymers have been reported (Hubert et al 2009;Gojny et al 2004). Yet there exist a number of challenges to be overcome in order for successful exploitation of the full potential of these tiny nanotubes of carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Out of many possible applications, mechanical reinforcement of polymers by incorporation of carbon nanotubes (CNTs) has received strong interest from the scientific community as well as the industry, especially since the beginning of the new millennium (Coleman et al 2006; Thostenson and Chou 2006;Gojny et al 2005;Chakraborty and Coleman 2008;Hubert et al 2009). What makes CNTs very interesting for composites is that even with a relatively low level of loading (ca.…”
Section: Introductionmentioning
confidence: 99%